Donor ABCB1 genetic polymorphisms influence epithelial-to-mesenchyme transition in tacrolimus-treated kidney recipients. (December 2014) - Bloch, Julie; Hazzan, Marc; Van der Hauwaert, Cynthia; Buob, David; Savary, Grégoire; Hertig, Alexandre; Gnemmi, Viviane; Frimat, Marie; Perrais, Michaël; Copin, Marie-Christine; Broly, Franck; Noël, Christian; et al.
Aim: The contribution of epithelial–mesenchymal transition (EMT) has been suggested in renal transplant recipients receiving calcineurin inhibitors and developing nephrotoxicity.Materials & methods: We assessed whether interindividual variability in tacrolimus pharmacokinetics is associated with the occurrence in tubular cells of two EMT markers (vimentin, β-catenin) detected at 3‐month in 140 allograft biopsies. We investigated whether genetic polymorphisms affecting CYP3A5 and ABCB1 influence EMT and kidney fibrosis.Results: In univariate analysis, the donor CYP3A5*1 allele was significantly associated with a lower vimentin expression. In multivariate analysis, grafts carrying ABCB1 3435T allele(s) developed significantly less EMT and less interstitial fibrosis.Conclusion: Donor SNPs significantly influence the epithelial program in the context of kidney transplantation, and the epithelial metabolism of tacrolimus is one key to understand graft fibrogenesis.